Label-free ultrasensitive detection of telomerase activity via multiple telomeric hemin/G-quadruplex triggered polyaniline deposition and a DNA tetrahedron-structure regulated signal. Issue 9 (23rd December 2015) - Liu, Yuanjian; Wei, Min; Liu, Xu; Wei, Wei; Zhao, Hongyu; Zhang, Yuanjian; Liu, Songqin
Abstract : Label-free ultrasensitive detection of telomerase activity via multiple telomeric hemin/G-quadruplex triggered polyaniline deposition and a DNA tetrahedron-structure regulated signal. Abstract : Label-free detection of telomerase activity was done by using telomeric hemin/G-quadruplex triggered polyaniline deposition, not only on themselves but also on the DNA tetrahedron-structure (DTS). DTS size has a great impact on telomerase accessibility, reactivity and detection sensitivity. The method has been used to evaluate bladder cancer development.